Visions, tensions and results. The new governance of education in Honduras - Morales Ulloa, Ricardo; Magalhães, António M. (Education Policy Analysis Archives, 2013)
Since the 1980s, as a direct consequence of the debt crisis, under the guidelines of multilateral organizations such as the World Bank and the International Monetary Fund, Latin America has experienced a series of reforms to replace the role of the state as the main driver to achieve socio-economic development by a new model of governance. This article examines the changes that took place in the educational system of Honduras in the past 20 years, under the influence of the so called process of modernization of education, initiated in the 1990. In 1996 this process resulted into the administrative de-concentration of education at the pre-school, primary and secondary levels. This paper examines the distinctive characteristics of this process in Honduras, a country pervaded with social, political and economic contradictions, and where the educational system has not been able to respond to the enormous demands of a society marked by exclusion. The analysis stresses the gap between the expectations of an educational policy that was intended to have an important and comprehensive impact and the very modest results that so far have been achieved.